The Role of Internal Audit in Reducing Social Media Risks (Suggested Actions) - Mohammed, Abdulwahid; Saleh, Manal (PROSPECTIVE RESEARCHES, 2024)
The study aims to determine the uses of social media in economic units, identify the risks associated with social media according to IIA publications, propose procedures for auditing social media and present proposed procedures to enhance security and manage risks effectively. These proposed procedures include improving preventive measures and strengthening digital security policies. Developing rapid response mechanisms to confront emerging challenges, which contributes to enhancing confidence in the use of social media within economic units